Eksperimentasi Penerapan Model Pembelajaran NHT (Numbered Heads Together) dan TGT (Team Games Tournament) Terhadap Prestasi Belajar Matematika di SMP Negeri 5 Ngawi - Indra Puji Astuti; Erny Untari (JEID: Journal of Educational Integration and Development, 2021)
The research aims was to find out the difference of learning model NHT (Numbered Heads Together) and TGT (Team Games Tournament) toward learning achievement. This research was a quasi-experimental with population was all students in Grade VIII SMP Negeri 5 Ngawi in academic year 2017/2018. A sample of 68 students was obtained using the simple random sampling technique. Data were collected using multiple choice tests. The data analysis techniques used t-test. With the 5% level of significance the result was students who were subjected to TGT (Team Games Tournament) learning model gave better mathematics learning achievement than students who were subjected to NHT (Numbered Heads Together) learning model. Before t-test, the normality test and homogeneity test were carried out first as a prerequisite test for analysis. Keyword: learning achievement, NHT (Numbered Heads Together), TGT (Team Games Tournament)